Uniqueness of Solutionfor Nonlinear Implicit Fractional Differential Equation - Tidke, Haribhau Laxman (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
We study the uniquenessof solutionfor nonlinear implicit fractional differential equation with initial condition involving Caputo fractional derivative. The technique used in our analysis is based on an application of Bihari and Medved inequalities.